2017
DOI: 10.19082/5578
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine on heart arrhythmia prevention in off-pump coronary artery bypass surgery: A randomized clinical trial

Abstract: BackgroundArrhythmia occurring during and after surgery is one of the major complications in open-heart surgery. Dexmedetomidine is an intravenous alpha-2 agonist and very specific short-acting drug to protect the various organs against ischemic injuries and blood reflow. However, the effect of dexmedetomidine for preventing intraoperative heart arrhythmias has not been recognized.ObjectiveThis study aimed to determine the effect of dexmedetomidine on the incidence rate of heart arrhythmias and anesthetic requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
(32 reference statements)
1
15
1
Order By: Relevance
“…17 However, our study found 8% incidence of arrhythmias. Administration of DEX is shown to reduce the arrhythmias in cardiac surgery patients by Liu et al 18 and Soltani et al 12 Our study did not found statistically different incidence of arrhythmias between both the groups .Shehabi et al 19 and Herr et al 20 also showed no correlation of administration of DEX and arrhythmias in cardiac surgery patients.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…17 However, our study found 8% incidence of arrhythmias. Administration of DEX is shown to reduce the arrhythmias in cardiac surgery patients by Liu et al 18 and Soltani et al 12 Our study did not found statistically different incidence of arrhythmias between both the groups .Shehabi et al 19 and Herr et al 20 also showed no correlation of administration of DEX and arrhythmias in cardiac surgery patients.…”
Section: Discussioncontrasting
confidence: 48%
“…11 Soltani et al, also proved lesser heart rate and preservance of MAP in DEX group than the control. 12 Similarly PRODEX, largest clinical trial comparing DEX and propofol, found DEX non substandard to propofol in terms of incidence of hypotension and bradycardia in mechanically ventilated patients. 13 However SPICE III trial found more incidence of hypotension and bradycardia(although the incidence was merely 2.7% and 5.1% respectively) In critically ill patients receiving DEX in comparison to usual care group patients.…”
Section: Discussionmentioning
confidence: 99%
“…All of the studies included patients that underwent open-heart cardiac surgery. Among them, ten RCTs included patients who underwent elective coronary artery bypass grafting (CABG) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), while the other five included patients who underwent mixed type of open-heart surgeries, including CABG, valvular surgeries, and aortic surgeries (10,16,(22)(23)(24).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The mean ages of the patients varied between 52 and 75 years, with proportions of male ranging from 32 to 90%. Mean body weight of the patients was reported in five studies (11,(13)(14)(15)22), while BMI was reported in another five studies (10,16,17,21,24). Dex was administered only during the procedure of surgery in two studies (13,23), only during the stay in Intensive Care Unit (ICU) in nine studies (10,12,(15)(16)(17)(19)(20)(21)(22), and during the surgery and ICU in four studies (11,14,18,24).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation